The Association Between Phosphorylated Neurofilament Heavy Chain (pNF-H) and Small Fiber Neuropathy (SFN) in Patients with Impaired Glucose Tolerance - Li, Yu-peng; Yan, Zhong-qing; Han, Li-ping; Yin, Ai-li; Xu, Jin-yong; Zhai, Ya-ran; Hao, Sai; Zhang, Lin; Xie, Yun (Diabetes therapy, 2020)
Introduction Small fiber neuropathy (SFN)—the early stage of diabetic peripheral neuropathy (DPN)—progresses gradually and is difficult to diagnose using neurophysiological tests. To facilitate the early diagnosis of SFN, biomarkers for SFN must be identified. The purpose of this study was to investigate the characteristics of SFN in prediabetic patients and the relationship between pNF-H and SFN. Methods 44 IGT patients (inpatients and outpatients) were selected at random. 33 healthy subjects served as controls. Data on clinical characteristics and laboratory parameters were collected. Quantitative sensory testing (QST), electromyography (EMG), and Sudoscan were performed, and pNF-H was measured by ELISA. Results 24 of the 44 patients with impaired glucose tolerance (IGT) were diagnosed with SFN according to the modified Toronto Diabetic Neuropathy Expert Group consensus criteria. The thermal sensory thresholds of the IGT-SFN group were significantly different from those of the CTRL group ( p < 0.05), except for the heat pain threshold. The sensory nerve action potential (SNAP) of the sural nerve was 12.39 in the IGT-SFN group, which was significantly lower than those in the other groups. No significant difference in nerve conduction velocity (NCV) was observed among the three groups. The electrochemical skin conductance (ESC) in the IGT-SFN group was 69.78 ± 14.03uS, which was significantly lower than that in the CTRL group. The pNF-H in the IGT-SFN group was 170.6 (140.0, 223.6) pg/ml, which was significantly higher than those in the CTRL and IGT-non-SFN groups (76.55 and 64.7 pg/ml, respectively). Multivariate regression analysis demonstrated that pNF-H and 2h plasma glucose were independently correlated with SFN; the ORs (95% CI) were 1.429 (1.315, 1.924) and 2.375 (1.157, 4.837), respectively. Conclusions Serum pNF-H may be associated with SFN in IGT patients, and serum pNF-H could therefore serve as a sensitive biomarker for the detection of SFN.